History, literature and emotions: literary imagination and historical imagination in Martha Nussbaum's Poetic Justice (Ágora Journal, 2023)
In Poetic Justice, Martha Nussbaum, similarly shaped by the experience of imaginative space, which invite us to know the same models of experience of the Others. Literature, in a sense, would allow us to experience vitality, impulses, charms, the time and, consequently, the historical experience in another way. Thus, whether as a possible condition of vision or the possibility of emotional experimentation, fiction experiences particular experiences together in a way that is creative, imaginative and imaginative. In this sense, the methodology that supports this essay is Paul Ricoeur’s phenomenological hermeneutics. Our objective is to propose the condition of access to a model of the possible that congratulates fiction, history and emotions from the creation of creation between imagination and historical imagination.
Keywords: history; literature; imagination